Paediatric inflammatory multisystem syndrome: temporally associated with SARS-CoV-2 (PIMS-TS) — A mimic of intra-abdominal malignancy. Issue 8 (26th August 2022) - Nasher, Omar; Friend, Amand; Lakshminarayanan, Bhanumathi; Turner, Kerry; Wood, Mark; Deri, Antigoni; Ingham, Danielle
Abstract : We report the case of a school-aged boy who presented with clinical features suggesting acute appendicitis. However, further imaging which included CT, demonstrated an inflammatory mass involving the transverse colon raising the suspicion of lymphoma. He then developed intestinal obstruction, and in view of the rapid progression of the disease, he was thought to have non-Hodgkin's lymphoma. He underwent an open excisional biopsy, which revealed a necroinflammatory process and no suggestion of lymphoma or an alternative malignancy or specific diagnosis. His steroid treatment was stopped, and he made a good recovery postoperatively. Positive COVID-19 antibodies, positive response to steroids, results and clinical features were consistent with paediatric inflammatory multisystem syndrome (PIMS-TS), with extensive investigation not offering an alternative diagnosis. While PIMS-TS is a relatively new entity, we believe that this case highlights the importance of it being considered a differential diagnosis of a child presenting with an inflammatory mass.